Difference between revisions of "Systems of differential equations"

From JSXGraph Wiki
Jump to navigationJump to search
Line 2: Line 2:
 
:<math> y_1'= f_1(x,y_1,y_2)</math>
 
:<math> y_1'= f_1(x,y_1,y_2)</math>
 
:<math> y_2'= f_2(x,y_1,y_2)</math>
 
:<math> y_2'= f_2(x,y_1,y_2)</math>
with initial values <math>(x_0,y_1)</math>, <math>(x_0,y_2)</math>.
+
with initial values <math>(x_0,c_1)</math>, <math>(x_0,c_2)</math>.
 
<html>
 
<html>
 
<form>
 
<form>
Line 12: Line 12:
 
var brd = JXG.JSXGraph.initBoard('jxgbox', {axis:true, boundingbox:[-11,11,11,-11]});
 
var brd = JXG.JSXGraph.initBoard('jxgbox', {axis:true, boundingbox:[-11,11,11,-11]});
 
var N = brd.create('slider',[[-7,9.5],[7,9.5],[-15,10,15]], {name:'N'});
 
var N = brd.create('slider',[[-7,9.5],[7,9.5],[-15,10,15]], {name:'N'});
var P1 = brd.create('point',[0,1], {name:'(x_0,y_1)'});
+
var P1 = brd.create('point',[0,1], {name:'(x_0,c_1)'});
 
var line = brd.create('line',[function(){return -P1.X();},function(){return 1;},function(){return 0;}],{visible:false});
 
var line = brd.create('line',[function(){return -P1.X();},function(){return 1;},function(){return 0;}],{visible:false});
var P2 = brd.create('glider',[0,2,line], {name:'(x_0,y_2)'});
+
var P2 = brd.create('glider',[0,2,line], {name:'(x_0,c_2)'});
  
 
function doIt() {
 
function doIt() {
Line 27: Line 27:
 
}
 
}
  
var g1 = brd.createElement('curve', [[0],[0]], {strokeColor:'red', strokeWidth:'2px', name:'y_1'});
+
var g1 = brd.createElement('curve', [[0],[0]], {strokeColor:'red', strokeWidth:'2px', name:'y_1', withLabel:true});
var g2 = brd.createElement('curve', [[0],[0]], {strokeColor:'black', strokeWidth:'2px', name:'y_2'});
+
var g2 = brd.createElement('curve', [[0],[0]], {strokeColor:'black', strokeWidth:'2px', name:'y_2', withLabel:true});
 
g1.updateDataArray = function() {
 
g1.updateDataArray = function() {
 
     var data = ode();
 
     var data = ode();

Revision as of 10:52, 21 July 2010

Display solutions of the ordinary differential equation

[math] y_1'= f_1(x,y_1,y_2)[/math]
[math] y_2'= f_2(x,y_1,y_2)[/math]

with initial values [math](x_0,c_1)[/math], [math](x_0,c_2)[/math].

f1(x,y1,y2)=
f2(x,y1,y2)=